GAMBARAN INTERAKSI SOSIAL LANSIA DI MASYARAKAT KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - M. Ilham; Sri Wahyuni; Arneliwati Arneliwati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Body function decrease along with the aging process and cause problems for the elderly, such as the lack of interaction with theenvironment.The purpose of the study was to determine the interaction of elderly people in society. This study used quantitative methods with descriptive research designs. This research conducted inPayung Sekaki district Pekanbaru. The sample of this study was 73 elderly. The instrument used was the elderly interaction questionnaire.The results of this study found that the age of the respondents who were the most busiest were 69 respondents (94.5%). The majority of respondents distribution were women with 47 respondents (64.4%). The highest distribution of respondent's work as an IRT were 40 respondents (54.8%). The results of the distribution of respondent's education were 22 respondents (30.1%). The distribution of the most elderly social interactions was good with 51 respondents (69.9%). The results of this study are expecting to be input for the elderly, families about social interaction, so that the elderly and families can increase their interaction with others. Keywords: overview of interactions, social, elderly